Biomimetic photonic materials derived from chitin and chitosan. Issue 3 (12th January 2021) - Lizundia, Erlantz; Nguyen, Thanh-Dinh; Winnick, Rebecca J.; MacLachlan, Mark J.
Abstract : Inspired by the natural hierarchical structures of chitin and cellulose found in nature, this Review summarizes recent progress to create biomimetic optical materials templated by nanochitin and compares it with developments using nanocellulose. Abstract : Insight into the hierarchical structures of carbohydrate nanofibrils such as chitin and cellulose is important in order to exploit their unique geometrical features for materials innovation and emerging applications. Chitin nanofibrils are responsible for the outstanding mechanical strength in exoskeletons of some animals, and for the iridescence of some insects. The appearance of structural colors in chitin-constituted insect shells inspires scientists to mimic their photonic properties in artificial analogues, paving the path towards new optical technologies. Although the intricate organization of chitin nanofibrils in these structures was recognized several decades ago, the use of chitin nanofibrils in biomimetic templating, to transfer their sophisticated structures into solid-state materials, has only recently been exploited. Cellulose nanocrystals (CNCs) are high aspect ratio nanomaterials prepared by acid hydrolysis of the most abundant carbohydrate in plants. Similar to chitin nanofibrils, CNCs are readily dispersible in water and present an intriguing self-assembly behavior that can be exploited as a lyotropic liquid-crystalline template to fabricate photonic materials. Extended efforts of this research strategy are necessary to seek new organized structures of carbohydrate nanofibrils and to develop synthetic methods that offer access to novel biomimetic materials that combine chirality, coloration, and mesoporosity through colloidal templating and self-assembly. This Review summarizes recent progress to create functional optical materials templated by nanochitin and compares it with developments using nanocellulose.